Apparent digestibility coefficient of practical diets with different energy: protein ratios for pirarucu juveniles - Ono, Eduardo Akifumi; Nunes, Érica da Silva Santiago; Cedano, Jimmy Carlos Campos; Filho, Manoel Pereira; Roubach, Rodrigo (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to determine the apparent digestibility of nutrients and energy of diets for pirarucu (Arapaima gigas) juveniles. Eight experimental diets containing four energy:protein ratios (11, 10.1, 9, 8 kcal digestible energy per gram of crude protein) and two non-protein energy sources (soybean oil and poultry fat) were tested in a 4x2 factorial scheme, in triplicates. Two hundred and forty pirarucu juveniles weighting 96.8±2.3 g were distributed in 24 cylindrical-conical fiberglass tanks, adapted for feces collection (modified Guelph system). Fish were fed twice a day to apparent satiation, with experimental diets containing 0.5% of chromium oxide as inert marker in order to determine the apparent digestibility coefficients. Diets containing an energy:protein ratio of 9 kcal digestible energy per gram of crude protein resulted in significantly lower apparent digestibility coefficient for dry matter, crude protein and non-nitrogenous extract. The highest apparent digestibility coefficients for crude fat was obtained with soybean oil. The dietary energy:protein ratio influences the nutrient and energy apparent digestibility coefficients to pirarucu juveniles.